2022
DOI: 10.1126/science.abl5470
|View full text |Cite|
|
Sign up to set email alerts
|

Ultrahard magnetism from mixed-valence dilanthanide complexes with metal-metal bonding

Abstract: Magnetic effects of lanthanide bonding Lanthanide coordination compounds have attracted attention for their persistent magnetic properties near liquid nitrogen temperature, well above alternative molecular magnets. Gould et al . report that introducing metal-metal bonding can enhance coercivity. Reduction of iodide-bridged terbium or dysprosium dimers resulted in a single electron bond between the metals, which enforced alignment of the other valence electrons. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
406
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 348 publications
(507 citation statements)
references
References 82 publications
13
406
3
1
Order By: Relevance
“…7–9 Layfield et al reported a dysprosium metallocene cation [(Cp iPr5 )Dy(Cp*)] + showing an exceptionally high anisotropy barrier U eff of 1541 cm −1 , and its 100 s blocking temperature T B is 65 K. 10 In 2022, Long, et al just reported one dilanthanide complex with metal–metal bonding whose energy barrier and blocking temperature are up to 1631 cm −1 and 72 K, respectively. 11 Recently, we also theoretically predicted that the energy barrier and blocking temperature of one two-coordinate [Co(C(SiMe 2 ONaphthyl) 3 ) 2 ] 12 can be enhanced up to 1559.1 cm −1 and 90 K, respectively, through the structural distortion. 13 To date, a lot of high-performance SIMs with high energy barriers and blocking temperatures are almost Dy III -based complexes.…”
Section: Introductionmentioning
confidence: 98%
“…7–9 Layfield et al reported a dysprosium metallocene cation [(Cp iPr5 )Dy(Cp*)] + showing an exceptionally high anisotropy barrier U eff of 1541 cm −1 , and its 100 s blocking temperature T B is 65 K. 10 In 2022, Long, et al just reported one dilanthanide complex with metal–metal bonding whose energy barrier and blocking temperature are up to 1631 cm −1 and 72 K, respectively. 11 Recently, we also theoretically predicted that the energy barrier and blocking temperature of one two-coordinate [Co(C(SiMe 2 ONaphthyl) 3 ) 2 ] 12 can be enhanced up to 1559.1 cm −1 and 90 K, respectively, through the structural distortion. 13 To date, a lot of high-performance SIMs with high energy barriers and blocking temperatures are almost Dy III -based complexes.…”
Section: Introductionmentioning
confidence: 98%
“…[1][2][3][4] This attention is not surprising, given the near-innite number of possible combinations of metals, ligands, and their spatial-orientations. It is precisely this diversity of constitutional and structural possibilities that has given rise to a wide range of physical properties and applications such as single-molecule magnets (SMMs), [5][6][7][8][9] luminescence, 10,11 and catalysis. 12,13 Importantly, with powerful design concepts, the properties of individual metal centers can be modulated through variations of experimental conditions and the structural environment, [14][15][16] thus entailing novel responsive compounds, which exhibit properties superior in complexity to their homometallic analogues and lower-nuclearity cognates.…”
Section: Introductionmentioning
confidence: 99%
“…These findings have major consequences for molecular magnetism practices. In addition to well established approaches to increase the axiality of the crystal field [102] and exchange coupling multiple ions [117], ab initio spin dynamics results point to the design of rigid molecular structures as key to reduce spin-phonon relaxation rates [71]. Indeed, by increasing molecular rigidity, optical modes are shifted up in energy with a two-fold effect: i) they become less admixed with acoustic modes [55], so reducing the rate of direct relaxation, and ii) they become less populated so that Raman relaxation rate would also slow down [56,57,107].…”
Section: Discussionmentioning
confidence: 99%